Differences in Supply Chain Material Risk Weight Using the Severity Index Method and Monte Carlo Simulation - Debataraja, Lisherly Reginancy; Purba, Marsedes; Amrizal; Budianto, Gallio (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Material delays are a significant challenge in completing construction projects, closely tied to the understanding of material supply flow. As a result, a risk weight analysis is essential, considering both internal factors (such as supply, control, processes, and demand) and external factors (such as disasters). This study began with a literature review to compile a list of potential risks, followed by data collection through a questionnaire administered to 50 experts in construction material procurement. The risk analysis was then conducted using both the Severity Index and Monte Carlo methods. The results showed average risk differences between the two methods: supply side (16.40% vs. 16.76%), control risk (16.28% vs. 11.53%), process risk (11% vs. 11.20%), demand risk (16.10% vs. 13.87%), and disaster risk (13.78% vs. 13.41%). The highest risk identified was in the supply side, specifically the extended waiting times due to staggered material deliveries, while the lowest risk was related to the process of ordering materials, where issues arise from the need for reordering based on inaccurate quantity information.